2002
DOI: 10.1007/s00267-002-2714-7
|View full text |Cite
|
Sign up to set email alerts
|

Farmers, Streams, Information, and Money: Does Informing Farmers About Riparian Management Have Any Effect?

Abstract: We assessed relationships between the extent to which farmers reported exposure to relevant information and their attitudes towards, knowledge about, and degree of adoption of riparian management strategies. We also examined associations between knowledge of, or receipt of, financial assistance for riparian fencing/planting and intentions for and extent of adoption of this strategy. A mail survey of 718 pastoral farmers in Otago and Southland in New Zealand [294 surveys returned (41%)] yielded 279 usable quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…A number of studies have looked at the decision of landowners to supply land based ecosystem services including riparian buffer zones and different factors have been found to influence the provision decision. For example, previous research has highlighted the importance of financial incentives in securing a change of land use from productive agriculture to the provision of an ecosystem service (Lynch et al, 2001;Genghini et al, 2002;Rhodes et al, 2002;Curtis and Robertson, 2003;Shultz, 2005;Sullivan et al, 2005;Kabii and Horowitz, 2006;Suter et al, 2008;Patrick andBarclay, 2009 Yu andBelcher, 2011). Others have suggested that intrinsic, political or ethical motivations around land stewardship take precedent over economic compensation (Ryan et al, 2003;Thomas and Blackmore, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have looked at the decision of landowners to supply land based ecosystem services including riparian buffer zones and different factors have been found to influence the provision decision. For example, previous research has highlighted the importance of financial incentives in securing a change of land use from productive agriculture to the provision of an ecosystem service (Lynch et al, 2001;Genghini et al, 2002;Rhodes et al, 2002;Curtis and Robertson, 2003;Shultz, 2005;Sullivan et al, 2005;Kabii and Horowitz, 2006;Suter et al, 2008;Patrick andBarclay, 2009 Yu andBelcher, 2011). Others have suggested that intrinsic, political or ethical motivations around land stewardship take precedent over economic compensation (Ryan et al, 2003;Thomas and Blackmore, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, institutional factors pertaining to how a specific programme is implemented was 6 found to influence potential adoption. These include length of scheme and planning horizon, potential development value, bureaucratic load, requirements associated with the scheme, flexibility of conditions, confidence in efficacy of recommended practices and funding certainty (Lynch et al, 2001;Ducros and Watson, 2002;Rhodes et al, 2002;Curtis and Robertson, 2003;Shultz, 2005;Mante and Gerowitt, 2009;Patrick and Barclay, 2009;Christensen et al, 2011;Yu and Belcher;.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, among many farmers, these services are not considered decisive factors in whether to plant or not (Carr & Tait, 1991;Fairweather, 1996). Farmers who do place a high value on these services are positively correlated with income (Rauniyar & Parker, 1998;Salam, Noguchi, & Alim, 2006;Underwood & Ripley, 2000;Vanslembrouck, Van Huylenbroeck, & Verbeke, 2002), education and conservation knowledge (Cable & Cook, 1997;Salam et al, 2006;Vanslembrouck et al, 2002;Wilson, 1992), and weakly correlated with information about incentive programmes and funding (Rhodes et al, 2002). Lower values among farmers are negatively correlated with farmer age (Cable & Cook, 1997;Wilson, 1992).…”
Section: Are the Resulting Woody Vegetation Network Significantly Comentioning
confidence: 99%
“…A minority of farmers also value their aesthetic services (Fairweather, 1996), and appreciate their soil conservation services (Mead, 1995). Primary barriers to planting trees are time and money (Fairweather, 1996;Rauniyar & Parker, 1998;Rhodes, Leland, & Niven, 2002;Underwood & Ripley, 2000). Some studies indicate financial incentives are inadequate to encourage farmers to take land out of production to plant trees (Duesberg, O'Connor, & Dhubháin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of compulsion, the voluntary motivation to undertake specific actions requires not just an attitude change but also a behaviour change (Rhodes et al 2002). When left entirely to voluntary mechanisms this shift in behaviour (adoption of action) is based on subjective rather than objective decision making and can be very slow (Pannell et al 2006).…”
Section: Farmer Identified Motivations For Planting Riparian Marginsmentioning
confidence: 99%